Sociological characteristics of alcohol‐induced suicide attempters: A retrospective study - Ryuichiro Narishige; Yasushi Otaka; Amane Tateno (PCN Reports)
Abstract Aim Although alcohol consumption is known to be a trigger for suicide, the extent to which acute alcohol consumption influences suicide attempts in Japan is unclear. We investigated the actual state and background of alcohol‐induced suicide attempts, that is, suicide attempts induced by acute alcohol consumption, in patients with severe suicide attempts admitted to the emergency department. Methods The subjects were suicide attempters over 20 years old who were admitted to the emergency department between 2010 and 2021. The means of suicide attempt, sociodemographic data, psychiatric diagnoses, and causes and motives of suicide attempts were retrospectively examined from medical records. We compared differences in the characteristics of data obtained from males and females with and without alcohol‐induced suicide attempts, and used logistic regression analysis to evaluate the influence of those factors on alcohol‐induced suicide attempts. Results Among the 801 suicide attempters over 20 years old during 2010 to 2021, 130 (16.2%) were alcohol‐induced suicide attempters: 61 (18.9%) of 323 male suicide attempters and 69 (14.4%) of 478 female suicide attempters. Substance‐induced disorders in both males and females, in addition to marital relations in males and living alone and personality disorders in females, had significant influence on alcohol‐induced suicide attempts. Conclusion Acute alcohol consumption was found to be a trigger in approximately one in six suicide attempts and alcohol‐induced suicide attempts were not unique in terms of substance dependence. We believe that focusing on those factors that seemed to influence alcohol‐induced suicide attempts in the present study could provide clues regarding the prevention of alcohol‐induced suicide attempts.